1989
DOI: 10.1177/1077727x8901700303
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Quarterly Household Expenditures on Apparel

Abstract: and Apparel Management, University of Columbia, MD 65211. This study provides an updated view of factors affecting U.S. clothing demand. The effects of various socioeconomic and demographic variables on household expenditures for apparel were examined. A theoretical model explicitly acknowledging the durable nature of clothing was presented. In addition, quarterly expenditures over a one-year period were examined, accounting for variations due to seasonality. Data from the 1980-81 Consumer Expenditure Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 6 publications
4
60
0
Order By: Relevance
“…Given the reliance of these studies on economic theory for a theoretical framework, some measure of income is typically included. As economic theory predicts, empirical support for a positive relationship between income (or total expenditures) and apparel expenditures was found (Dardis et al, 1981;DeWeese, 1993;DeWeese and Norton, 1991;Douthitt and Fedyk, 1988;Nelson, 1989;Norum, 1989Norum, ,1992Wagner and Hanna, 1983;Zhang and Norton, 1995). Total consumption expenditures, used in several studies to proxy income (Dardis et aL, 1981;Nelson, 1989;Wagner and Hanna, 1983), provide a better fit in models built for prediction purposes (Dardis et al, 1981).…”
Section: Previous Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…Given the reliance of these studies on economic theory for a theoretical framework, some measure of income is typically included. As economic theory predicts, empirical support for a positive relationship between income (or total expenditures) and apparel expenditures was found (Dardis et al, 1981;DeWeese, 1993;DeWeese and Norton, 1991;Douthitt and Fedyk, 1988;Nelson, 1989;Norum, 1989Norum, ,1992Wagner and Hanna, 1983;Zhang and Norton, 1995). Total consumption expenditures, used in several studies to proxy income (Dardis et aL, 1981;Nelson, 1989;Wagner and Hanna, 1983), provide a better fit in models built for prediction purposes (Dardis et al, 1981).…”
Section: Previous Researchmentioning
confidence: 94%
“…Total consumption expenditures, used in several studies to proxy income (Dardis et aL, 1981;Nelson, 1989;Wagner and Hanna, 1983), provide a better fit in models built for prediction purposes (Dardis et al, 1981). The magnitude of expenditure elasticities tends to be greater than unity (Dardis et al, 1981;Nelson, 1989), whereas the magnitude of income elasticities tends to be less than unity (Dardis et al, 1981;Norum, 1989;Zhang and Norton, 1995). In addition to the income measure, a variety of socioeconomic and demographic factors, such as age, family size, education, occupation, and region, were included in the analyses.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Dardis~ 2J.. (1981), Chen and Chu (1982), and Norum (1989) found a negative relationship between c lothing expenditure and age. According to the findings of this study, elderly households also spent less on clothing than did younger ones.…”
Section: Discussionmentioning
confidence: 99%
“…Expenditure on clothing was negatively related to age. Norum (1989), who analyzed 1980-81 data, found that clothing expenditure of elderly hous eholds was lower than those of other age groups .…”
Section: Previous Researchmentioning
confidence: 99%